Alternative leachate treatment using cement kiln dust - Nurul Muhammad, Ahmad (2012)
The generation of solid waste that increasing concurrently with increasing of population due to activity of human and animals. Due to open dumping problem in Malaysia, it is feared that untreated leachate that generated will harm the ecosystem. The major part in leachate treatment is chemical treatment that comprised such coagulation-flocculation, chemical precipitation and oxidation. The rugh composition of calcium oxide, CaO in CKD is found to be most important parameter in determination of this product to be an effective coagulant. Hence, the current coagulation-flocculation process in leachate treatment effectiveness could be increase. The main focus of this study is to determine the suitability of cement kiln dust as coagulant in coagulation-flocculation process in leachate treatment. The results are prior to percentage removal of BOD, COD, TSS and manganese. Coagulation-flocculation was performed in a standard jar-test apparatus comprising of six paddle rotors (24.5 x 63.5 mm) and equipped with 6 beakers, using 1000 mL of leachate sample. The agitation speed (rapid and slow mixing) and settling time were selected as 300 rpm for l min before adding CKD doses at 1, 2, 3, 4, 6, and 8g followed by flash mixing for I 0 minutes and I 0 rpm for 1 min and finally settling for 60 min. Thus, the optimum coagulant doses and effect of contact time in this process are revealing. The optimum dosage of CKD is found to be 2 g/L which the percentage of BOD, COD, TSS and manganese (Mn) removal is up to 6.88%, 92.04%, 83.63% and 98.13% respectively. All parameter tested for wastewater leachate such as BOD, COD, TSS and heavy metal which is Manganese (Mn) is showing high percentage removal by coagulation-flocculation process (es) by using CKD as coagulant.